2004
DOI: 10.1038/nature02125
|View full text |Cite
|
Sign up to set email alerts
|

A large population of ‘Lyman-break’ galaxies in a protocluster at redshift z ≈ 4.1

Abstract: The most massive galaxies and the richest clusters are believed to have emerged from regions with the largest enhancements of mass density relative to the surrounding space. Distant radio galaxies may pinpoint the locations of the ancestors of rich clusters, because they are massive systems associated with 'overdensities' of galaxies that are bright in the Lyman-alpha line of hydrogen. A powerful technique for detecting high-redshift galaxies is to search for the characteristic 'Lyman break' feature in the gal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
109
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 21 publications
1
109
0
Order By: Relevance
“…It has been suggested that this source is associated with a highly overdense region traced by LAEs and Lyman-break galaxies (LBGs), and thus represents an ancestor of present-day clusters, i.e. a protocluster (Venemans et al 2002(Venemans et al , 2007Miley et al 2004;Intema et al 2006;Overzier et al 2008). Theoretical simulations also suggests that the overdensity associated with TNJ1338 is likely to be an ancestor of a present-day cluster (Chiang, Overzier & Gebhardt 2013).…”
Section: Introductionmentioning
confidence: 89%
“…It has been suggested that this source is associated with a highly overdense region traced by LAEs and Lyman-break galaxies (LBGs), and thus represents an ancestor of present-day clusters, i.e. a protocluster (Venemans et al 2002(Venemans et al , 2007Miley et al 2004;Intema et al 2006;Overzier et al 2008). Theoretical simulations also suggests that the overdensity associated with TNJ1338 is likely to be an ancestor of a present-day cluster (Chiang, Overzier & Gebhardt 2013).…”
Section: Introductionmentioning
confidence: 89%
“…Chapman et al 2000;Hall et al 2001). Overdensities of Hα emitters (Kurk et al 2004a;Tanaka et al 2011), Lyman Break Galaxies (Miley et al 2004), BzKselected sources (Galametz et al 2009) and red sequence galaxies (Doherty et al 2010) have also been reported in the vicinities of HzRGs. Large rotation measures within the HzRG environments (Carilli et al 1997) are indicative of dense, X-ray emitting cluster atmospheres.…”
Section: Introductionmentioning
confidence: 97%
“…Jiang et al 2007;Kurk et al 2007). Overdensities (of the order of a few) of star-forming galaxies suggest that at least some RGs are associated with rare peaks in the large-scale structure (e.g., Pentericci et al 2000;Miley et al 2004;Venemans et al 2002Venemans et al , 2007. Similarly, the number counts of faint i-dropouts toward two z ∼ 6 QSOs (Stiavelli et al 2005;Zheng et al 2006;Kim et al 2009) also indicate a possible enhancement (see Overzier et al 2009, for a detailed discussion).…”
Section: Introductionmentioning
confidence: 99%